Harnessing the immunomodulatory properties of HLA-G for advanced immunotherapies - Beli, Xeni; Savvopoulos, Nikolaos; Kefala, Dionysia; Lysandrou, Memnon; Liga, Maria; Spyridonidis, Alexandros (Frontiers in Immunology, 2025)
Human leukocyte antigen-G (HLA-G) is a non-classical MHC class I molecule with unique immunomodulatory properties that extend far beyond its well-established role at the maternal-fetal interface. Increasing evidence highlights HLA-G as a pivotal regulator of immune homeostasis, capable of shaping both innate and adaptive cytotoxic responses. It exerts a context-dependent role, promoting tolerance in settings such as transplantation and autoimmunity while contributing to immune evasion in cancer and infection, and this functional plasticity is further shaped by its isoform diversity and its interplay with other non-classical HLA class I molecules. In this review, we discuss key aspects of HLA-G biology, particularly its capacity to promote immune tolerance or facilitate immune escape, and how these insights can be leveraged in the development of cellular and acellular immunotherapies. We further summarize current strategies that incorporate or target HLA-G in the treatment of malignancies and autoimmune diseases, and highlight its emerging potential as a therapeutic target.